2021
DOI: 10.1101/2021.01.17.426995
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards a mathematical understanding of colonization resistance in multispecies microbial communities

Abstract: Microbial community composition and dynamics are key to health and disease. Explaining the forces generating and shaping diversity in the microbial consortia making up our body’s defenses is a major aim of current research in microbiology. For this, tractable models are needed, that bridge the gap between observations of patterns and underlying mechanisms. While most microbial dynamics models are based on the Lotka-Volterra framework, we still do not have an analytic notion of colonization resistance, by which… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
(159 reference statements)
0
4
0
Order By: Relevance
“…Data accessibility. Data and codes related to this study can be found on the Dryad Digital Repository: https://doi.org/ 10.5061/dryad.0k6djhb60 [65].…”
Section: Discussionmentioning
confidence: 99%
“…Data accessibility. Data and codes related to this study can be found on the Dryad Digital Repository: https://doi.org/ 10.5061/dryad.0k6djhb60 [65].…”
Section: Discussionmentioning
confidence: 99%
“…When there is just variation in co-colonization coefficients k ij , we recover the model and the Θ in (Madec and Gjini, 2020). Further, recall in (Madec and Gjini, 2020) the term z T Λz is denoted as Q and referred to as mean invasibility of the system, also revisited in terms of colonization resistance (Gjini and Madec, 2021b). In the 2-strain system, more explicitly we have:…”
Section: Parametermentioning
confidence: 99%
“…When there is just variation in co-colonization coefficients k ij , we recover the model and the Θ in (Madec and Gjini, 2020). Further, recall in (Madec and Gjini, 2020) the term z T Λz is denoted as Q and referred to as mean invasibility of the system, also revisited in terms of colonization resistance (Gjini and Madec, 2021b). In the 2-strain system, more explicitly we have: Q = z T Λz = (λ 2 1 + λ 1 2 )z 1 z 2 , and this quantity is positive only in the case of coexistence between two strains.…”
Section: Parametermentioning
confidence: 99%
“…When there is just variation in co-infection susceptibility coefficients k ij , we recover the model and the Θ in (Madec and Gjini, 2020). Further, recall in (Madec and Gjini, 2020) the term z T Λz is denoted as Q and referred to as mean invasibility of the system, capturing resistance of the system to invasion by outsiders (Gjini and Madec, 2021b). In the 2-strain system, more explicitly we have:…”
Section: Pairwise Invasion Fitness and Replicator Dynamics Via Timescale Separationmentioning
confidence: 99%